Implementation of Teaching Games For Understanding (TGFU) Through Soccer Like Games on the Decision-Making Level of Elementary School Students - Puput Melati Saputri; Lukmannul Haqim Lubay; Suherman Slamet (Universitas Negeri Semarang, 2025)
This study aims to determine the effect of implementing the Teaching Games for Understanding (TGFU) model through Soccer Like Games on students’ futsal playing skills. The research design used was an experiment with a one-group pre-test and post-test model. The subjects were 30 fourth and fifth grade students of the futsal extracurricular at YWKA Elementary School in Bandung City who were selected using a purposive sampling technique. The research instrument used the Game Performance Assessment Instrument (GPAI) which assesses three aspects of playing skills, namely decision making, skill execution, and support. Data were collected through direct observation during the game and analyzed using SPSS version 21 with the Shapiro-Wilk normality test, homogeneity test, and Paired Sample t-test at a significance level of 0.05. The results showed a significant improvement in students’ futsal playing skills after implementing TGFU learning through Soccer Like Games, with the average score increasing from 9.19 (pre-test) to 12.88 (post-test) (p < 0.05). This learning model is effective in improving decision-making skills, skill execution, and support in game situations. These findings recommend the implementation of TGFU as an alternative to physical education learning, especially in game sports.